2012
DOI: 10.1021/cn300103e
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Modification of the M1 Agonist VU0364572 Reveals Molecular Switches in Pharmacology and a Bitopic Binding Mode

Abstract: ABSTRACT:We previously reported the discovery of VU0364572 and VU0357017 as M 1 -selective agonists that appear to activate M 1 through actions at an allosteric site. Previous studies have revealed that chemical scaffolds for many allosteric modulators contain molecular switches that allow discovery of allosteric antagonists and allosteric agonists or positive allosteric modulators (PAMs) based on a single chemical scaffold. Based on this, we initiated a series of studies to develop selective M 1 allosteric an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…Three activators of mAChRs were administered: VU0364572, an M 1 -selective bitopic agonist [10,19], BQCA, an M 1 -selective PAM [12] and VU0152100, an M 4 -selective PAM [20]. The three doses for each drug were selected based on previous behavioral studies with these drugs [8,11,12,21].…”
Section: Methodsmentioning
confidence: 99%
“…Three activators of mAChRs were administered: VU0364572, an M 1 -selective bitopic agonist [10,19], BQCA, an M 1 -selective PAM [12] and VU0152100, an M 4 -selective PAM [20]. The three doses for each drug were selected based on previous behavioral studies with these drugs [8,11,12,21].…”
Section: Methodsmentioning
confidence: 99%
“…Early studies suggested that M 1 -receptor allosteric agonists may have major advantages over orthosteric M 1 -receptor agonists as they are comparatively more selective for the M 1 -subtype receptors 3236 ; however, most M 1 -receptor allosteric agonists are so-called ‘bitopic ligands’ that bind simultaneously both to an allosteric site and to the orthosteric site 3739 and require engagement of the orthosteric site for their activity. In these cases, the compounds bind to the orthosteric sites across all mAChR subtypes, but exhibit functional selectivity for certain subtypes 38 . Most M 1 -receptor bitopic agonists tend to act as weak partial agonists at M 1 receptors and exhibit only weak agonist activity in systems where M 1 receptors are expressed with low receptor reserve.…”
Section: Allosteric Modulator Pharmacologymentioning
confidence: 99%
“…Most M 1 -receptor bitopic agonists tend to act as weak partial agonists at M 1 receptors and exhibit only weak agonist activity in systems where M 1 receptors are expressed with low receptor reserve. Owing to this weak partial agonist activity, allosteric agonists can suffer from the same problems as do traditional M 1 -receptor orthosteric agonists and it can be difficult to achieve high selectivity 38 . Although it is not yet clear whether the same loss of selectivity would be observed with allosteric agonists of other receptor subtypes, these findings present major issues for the optimization of M 1 -receptor bitopic agonists as drug candidates owing to dose-limiting off-target activity; however, this problem could be avoided by M 1 -receptor PAMs or ago-PAMs, as long as they do not engage the acetylcholine (ACh) binding site.…”
Section: Allosteric Modulator Pharmacologymentioning
confidence: 99%
“…Such switches are by no means limited to mGlu 5 ; significant examples have been reported for the group II and III metabotropic glutamate receptors as well (68, 69). Indeed, the phenomenon of mode switching appears to be relatively widespread across a diverse set of targets for allosteric ligands, including muscarinic receptors, chemoattractant receptors, and voltage-gated potassium channels (70-73). This research has generated a large body of SAR data, but a unified vision of the underlying ligand-receptor interactions that cause mode switching has yet to be elucidated for these targets.…”
Section: The Emerging Complexity Of Designing Allosteric Ligands For mentioning
confidence: 99%